If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -1a = 13 Solving 16 + -1a = 13 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -1a = 13 + -16 Combine like terms: 16 + -16 = 0 0 + -1a = 13 + -16 -1a = 13 + -16 Combine like terms: 13 + -16 = -3 -1a = -3 Divide each side by '-1'. a = 3 Simplifying a = 3
| 8/3y-6=10 | | 2.17+9.6x+0.6x^5=0 | | 6a-21=9 | | .75x+2=.33x-8 | | -2(4n-8)=18 | | 3/4x+2=1/3x-8 | | 3ln(5x)= | | 9x^2-5x+4=0 | | 15=7-(c+9) | | 2x+28+3-14=180 | | 64-(4x+4)=4(x+6)+x | | 3x+1/2*3=0 | | 5x+20y=28c | | (w-1)(w-1)= | | 1/2ms | | X-x^2=42 | | 16-1/3x=11 | | 2/5sm | | 13x^2-840x-5040=0 | | 3(w-6)-5w= | | R(1-DT)=D | | -5x+8=3-4x | | 2/3x-84 | | 17-1/3x=11 | | x(x+6)=(x+3)2 | | 56t+62t=42 | | 6(x+3)+2=-16 | | 25x-8-16x+3=25x-4-16x+13 | | %nbsp;= eg;[3] | | -6-y=13 | | x^2+2.4x+1.44=0 | | 22=-7v+5(v+6) |